Transisi ke Coretax dan Pengaruhnya terhadap Tingkat Kepatuhan Wajib Pajak di Tengah Perubahan Hukum Pajak yang Ketat - Allaysha Adindaputri Kirani; Gunardi Lie (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2026)
The digital transformation of taxation through Coretax represents the government’s effort to improve efficiency and taxpayer compliance through a technology-based integrated system. However, this transition process also presents challenges in the form of taxpayers’ technical readiness and potential legal risks that could affect compliance levels, necessitating a review to support the optimization of government revenue. The objective of this study is to analyze the transition to Coretax and its impact on taxpayer compliance levels amidst stringent changes in tax laws. This study employs a normative legal method, specifically by examining relevant legal rules, principles, and doctrines to address issues related to the Coretax transition and taxpayer compliance. The results of this study indicate that the transition to Coretax has the potential to enhance taxpayer compliance through strengthened formal compliance and transparency in tax administration; however, its impact remains uneven, particularly for SMEs that still face limitations in technological access, digital literacy, and financial capacity. Amid tightening tax regulations, taxpayers’ technical unpreparedness may increase the risk of administrative or criminal sanctions, even though the issues that arise are more technical in nature than intentional. Therefore, it is necessary to strengthen the Coretax system, clarify the mechanisms for penalty relief, and enhance education, outreach, and technical assistance, accompanied by transparent and fair law enforcement to encourage voluntary compliance and optimize government revenue.